2004
DOI: 10.1007/s00247-004-1182-z
|View full text |Cite
|
Sign up to set email alerts
|

Persistent renal cortical scintigram defects in children 2 years after urinary tract infection

Abstract: Renal cortical scintigraphic defects persisted in approximately one-quarter of young children after their first proven urinary tract infection. The associated clinical features, however, failed to predict scar formation. It is possible that some of the scintigraphic defects preceded the infection by arising from either previously undiagnosed acute pyelonephritis or from underlying congenital dysplasia. The etiology of scars may be best addressed by determining whether prevention of urinary tract infections fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
5

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 41 publications
1
19
1
5
Order By: Relevance
“…This opinion is supported by the report by Jodal et al identifying clear relationship between renal scarring and VUR and 66% of children with high grade VUR developed a renal scarring compared with 5% of children without VUR [12]. On the contrary, Ditchfield et al reported that although VUR may predispose patients to acute pyelonephritis, no association was established between the presence of VUR and persistent renal cortical defects [1]. Although we have not analyzed genetic susceptibility as the risk factor for ASL and USF several reports demonstrated the role of genetic susceptibilities as clinical determinants explain only a portion of individual risk [25].…”
Section: Discussionmentioning
confidence: 64%
“…This opinion is supported by the report by Jodal et al identifying clear relationship between renal scarring and VUR and 66% of children with high grade VUR developed a renal scarring compared with 5% of children without VUR [12]. On the contrary, Ditchfield et al reported that although VUR may predispose patients to acute pyelonephritis, no association was established between the presence of VUR and persistent renal cortical defects [1]. Although we have not analyzed genetic susceptibility as the risk factor for ASL and USF several reports demonstrated the role of genetic susceptibilities as clinical determinants explain only a portion of individual risk [25].…”
Section: Discussionmentioning
confidence: 64%
“…A further difficulty of the scintigraphy studies (including the present research) is to make the distinction between acquired renal scarring and congenital dysplasia in patients with persistent photon defect on DMSA scintigraphy [9]. Without exact patient history or previous imaging, the aetiology of scars cannot always be determined.…”
Section: Discussionmentioning
confidence: 89%
“…However, female gender may be possibly associated with LUTD but not with renal scarring. In fact, Ditchfield et al [14] analyzed renal scarring in 196 children following they first UTI and after stratifying renal scarring by age, they reported no association between renal scarring and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Children with shrunken kidney or renal atrophy and diffuse scarring had been discharged and did not take part in this study. This was to exclude the possibility of bias due to congenital renal damage rather than postnatally acquired damage [13][14][15][16].…”
Section: Methodsmentioning
confidence: 99%